Economic Evaluations of Health Service Interventions Targeting Patients with Multimorbidities: A Scoping Literature Review - Lucia Ferrara; Vittoria Ardito; Valeria D. Tozzi; Rosanna Tarricone (International Journal of Integrated Care)
Introduction: Multimorbid patients have been growing, leading to an exponential increase in healthcare costs and patterns of resource utilization. Despite the heightened interest toward integrated care programs as a response to the complex need of multimorbid patients, economic evaluations of these programs remain scarce. This work investigated the economic evaluations of service interventions targeting multimorbid patients, to identify the characteristics of these programs and the methods applied to their evaluation. Methods: We conducted a scoping review of papers published between 2010 and 2021 on PubMed, Science Direct, EconLit and Web Of Science. The search strategy was built around three keyword blocks: service interventions, multimorbidity, economic evaluations. We selected economic evaluations of service interventions delivered through multiple care settings and targeting patients with 2+ chronic conditions. Results: Twenty-five articles were included. Interventions were categorized as organizational-type versus patient-oriented. The selected studies often targeted patients with one chronic disease, associated with a mental disorder, like depression or anxiety. Included studies were mostly cost-utility analyses conducted with the healthcare perspective. Discussions and conclusions: This work confirmed that economic evaluations of service interventions for multimorbid patients are limited in number. This could suggest that decision-making regarding the delivery of healthcare services for multimorbid patients may not always be based on a solid evidence base. More economic analyses are needed to inform evidence-based coverage decision-making.